Uréia de liberação lenta em substituição ao farelo de soja na dieta de terminação de novilhos Nelore confinados - Henrique de Oliveira Azevedo (2014)
The effect of replacing soybean meal by slow-release urea (SRU) in the diet of beef cattle finished in feedlot was evaluated in the period of July to November 2012. 48 uncastrated Nelore cattle were used, with an average age of 22 months, and a starting weight of 367.95 + 18.52 kg. The animals were kept in pens of 90 m² each, being three animals per pen. A completely randomized experimental arrangement was used, consisting of 12 repetitions per treatment (48 animals) for evaluation of the performance characteristics and food cost, and 8 repetitions per treatment (32 animals) for carcass characteristics. The treatments were: SM - 8.91% of soybean meal and 0% SRU; OP33 - 6.01% soybean meal and 0.46% SRU; OP67 - 2.94% soybean meal and 0.94% SRU; OP100 - 0% soybean meal and 1.41% SRU. The treatment effects were evaluated by linear and quadratic regression. There was no significant difference (P >0.05) between treatments for the variables initial weight, final weight, total gain, average daily gain, carcass gain, dry matter intake in kg/day, dry matter intake as a percentage of live weight, feed conversion, biological efficiency, hot carcass weight, carcass yield, front, special rear, needle tip, ribeye area, backfat thickness, and feed cost (R$/arroba). The slow release urea can replace up to 100% soybean meal in diets for feedlot cattle not affecting performance, carcass characteristics and feed cost of arroba produced.